The approach of the Turkish ministry of national education to translation in the teaching of literature - Ayan, Müge. (Thesis (M.A.) - Bogazici University. Institute of Social Sciences, 1999., 1999)
Since translation is a mode of transfer with the help of which the works produced by other cultures are imported into one's home system, translated literature in a sense shapes the literary paradigm; this is why it has an undeniable importance in the literary system, and therefore in the education of literature. Taking this as the starting point of my study I aim to reveal the approach of the Turkish Ministry of National Education to 'translation', and thus to determine how translation is reflected in the practice of literature teaching. With this purpose in mind, in the fITst chapter of the study, the curricular programs from 1924 to 1999 --published by the Turkish Ministry of National Education-are analyzed. It is concluded that, in the curricula, the conception of the 'universe' is limited to the 'West'; 'literature' is reduced either to 'Western literature' or to 'national literature' . This indicates that literature is not seriously regarded as a universal phenomenon. Moreover, the entire conception of '"World Literature" in the current program refers to foreign literature that is used for the sake of impressing nationalist values. In the second chapter, the textbooks themselves written in accordance with the curricula are analyzed. In the fITst part, a descriptive study of the translated literature presented in the literature textbooks read from the 1930s until the present day is carried out. The criteria that are applied in the selection of the translated texts have proved out to be 'canonicity' and 'nationality'. The descriptive study of the textbooks has again revealed that, under the label of 'universality' and 'humanity', only 'Western literature' is taught to students. As for the Ministry's understanding of 'translation', it can be observed that most of the names of the translators are specified from the 1940s to the 1980s; therefore, the position of the 'translator' is not totally disregarded. However, the analysis which aims to reveal the current position has shown that the name of the translator is not quoted: According to today's approach the position of the 'translator' is wholly disregarded. In the second part of Chapter Two with the aim of carrying out a comprehensive study, foreign texts that are presented to the students as 'adaptations' are analyzed; and it is discovered that, when the place names and names of characters are domesticated, 'translations' are referred to as 'adaptations'. This is indicative of the normative approach of the Ministry, which fails to consider 'translation' as a cultural activity, and reduces it to a linguistic activity. The study concludes with the evaluation of the data gathered from the descriptive studies, and suggestions are made concerning the problems caused by the Turkish National Education system in its approach to translation.
Keywords: Turkish literature -- Study and teaching.; Translating and interpreting.